Students Error Analysis in Using Adjective Clauses “Who and Whom” In Present Continues Tense - Halimah, Nur (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
dominant kinds of errors and the cause of errors made by the first grade of MA Integral Hidayatullah Makbusun. The data were taken from the erroneous adjective clauses “who and whom” in present continues tense . The test was given by the researcher to the students at MA Integral Hidayatullah Makbusun in the first grade that consists of fifteen students. In analyzing the data, the writer took the result of student test as technique of collecting data. The writer calculated the frequency of errors for each kind and also counted the percentages of errors in the form of table to determine the dominant kind of errors. Finally, the researcher analyzed the cause of errors. After analyzing the data, the researcher found 56% in used who and 69% in used whom. The researcher found kinds of errors There are addition (20 errors or 11.76 %), ommision (44 errors or 25.88 %), subtitution (69 errors or 40.59 %) and ordering (37 error or 21.76%). Therefore, the subtitution error has the highest frequency (69 errors or 40.59%). It proved that the students do not understand the pattern and function of adjective clauses “who and whom” sentence since they often ignore to put an item needed in the well-formed adjective clause sentence. In this research, the writer found that those errors are caused the cause by three types, that is first language interference, overgeneralization, and ignorance of rule restriction. And factors cause of error are interlangual transfer and intralingual transfer. Interlangual transfer is the errors caused by the mother tongue influence. While, intralingual transfer is the error caused by the target language influence.